Understanding, integrating and practicing Information Literacy (IL) resource-based projects in secondary schools / Halida Yu, Siti Arpah Noordin and Sobariah Awang Mukhtar - Yu, Halida; Noordin, Siti Arpah; Awang Mukhtar, Sobariah (Research Management Institute (RMI), 2011)
Rapid technological change has greatly affected and altered today's education system. Students live in a technology advanced and information abundance environment. The American Association of School Librarians and the Association for Educational Communication and Technology (1998), states that: "Contemporary learning theory describes tlie student as an active and engaged information user and underscores tlie importance of student's developing information expertise. Cognitive psychologists define learning itself as the active building of knowledge through dynamic interaction information and experience. Tlieorists in tlie information field contend that tlie information search process mirrors this description of tlie learning process: students actively seek to construct meaning from tlie sources tliey encounter and to create products that shape and communicate that meaning effectively. Core elements in both learning and information tlieory thus converge to suggest that developing expertise in accessing, evaluating, and using information is in fact tlie autlientic learning that modern education seeks to promote", (p.2).